Enhanced Electrochemiluminescence of Luminol on Indium Tin Oxide Modified with Dendrimer‐Encapsulated Au Nanoparticles. Issue 9 (26th June 2015) - Lee, Soon Bo; Kwon, Jihye; Kim, Joohoon
Abstract Enhanced electrochemiluminescence (ECL) of luminol was reported with the use of dendrimer‐encapsulated Au nanoparticle (Au DEN)‐modified ITOs in the presence of hydrogen peroxide, which was applied for sensitive ECL‐based electroanalysis of hydrogen peroxide. The enhanced ECL of luminol in the presence of hydrogen peroxide was attributed to facile electrochemical oxidation of luminol/hydrogen peroxide on the Au DEN‐modified ITOs at potentials as low as ∼0.4 V (vs. Ag/AgCl). Spooling ECL spectroscopy measurements indicated that the enhanced ECL emission of luminol/hydrogen peroxide system on the Au DEN‐modified ITOs originated from excited 3‐aminophthalate as same as that obtained on bare ITOs. Stability of Au DENs on ITO surfaces was also addressed and found to be closely related with the presence of chloride ions in electrolyte solutions.